A SIMULATION MODEL FOR MAPPING CARBON DIOXIDE EMISSIONS TO DEVELOP A GREEN LOGISTICS SYSTEM - Chen, Yang (My University, 2014)
The aim of this thesis is to develop a simulation tool that helps companies to track and re-evaluate the environmental impacts on their logistics systems. A discrete event based simulation model is used and developed in this thesis and it provides a simple and visible solution to map the carbon emission footprints and calculate carbon emission values throughout an outbound logistics distribution network. The total carbon emission level in a simplified logistics distribution system is primarily determined by the total transport distance and different emission factors which categorized by many other important parameters such as load factor, empty trip rate, batch size, vehicle type and fuel consumption rate and so on. By visualizing carbon emission footprints and understanding how the carbon emission values in different transport paths are accumulated in the whole distribution system, the developed simulation model helps supply chain and logistics planners to investigate their current logistics systems and identify improvement areas in their systems to lead a better and greener logistics design. Website-based simulation software is also purposed as future research recommendation for realistic industry use.
Keywords: Carbon Emission; Simulation; Logistics Network Design; Distribution System; ExtendSim.; fi=Tuotantotalous|en=Industrial Management|; fi=Master's Degree Programme in Industrial Management|